Implementasi Peraturan Penyelamatan Anak Pasca Bencana Konflik Sosial: Studi Kasus di Kecamatan Batee dan Kecamatan Tiro Kabupaten Pidie - Lisa Rahmi; Agussabti Agussabti; Saleh Syafei (Universitas Serambi Mekkah, 2018)
Social conflict is violence hostility between two groups or more of society that is continued in specific times and it impacts widely that caused unsafty and disintegration of social that can disturb national stability and blocked national construction. The research entitled “the implementation of children rescuiring policy pasca social conflict calamity in Aceh (case study in subdistric of Batee and Tiro Pidie regency)” purposed to detect how far the implementation of conflict children rescuing policy in Aceh, specially in Pidie regency. This research used qualitative method that use purposive sampling as the way how object research was choose here the researcher interviewed the regent governor, law department, education department, women and children empowerment department, department of Aceh reconciliation reinforcement (BP2A) and the people in the society that experienced conflict from the result of the research is knew that the implementation of policy of rescuing children after conflict was set in regulation governor of Aceh No 55 in 2012 about helps for children of disaster victim, No 53 in 2012 about help and protection to father less children, motherless children, orphan and poor families and the Qanun of Aceh No 11 in 2008 about children protection.